"I think we still do too little": measures to prevent violence and aggression in German emergency departments - a qualitative study - Sonja Reißmann; Tanja Wirth; Vanessa Beringer; David A. Groneberg; Albert Nienhaus; Volker Harth; Stefanie Mache (BMC, 2023)
Abstract Background Healthcare workers employed in emergency departments (EDs) are particularly affected by physical and verbal violence. Violent assaults can be committed by both patients and their attendants. Research on interventions for violence prevention is limited and previous studies report that ED employees feel unprepared for violent incidents. Thus, the current study aims to explore ED staff's perceptions regarding available prevention measures, their effectiveness, barriers, and further needs in terms of violence prevention. Methods In accordance with the qualitative study design, 27 semi-structured interviews were conducted via telephone with doctors and nurses working in direct contact with patients in German EDs. Main subjects were advantages and disadvantages of currently available measures, barriers regarding their implementation, their perceived effectiveness, as well as further needs concerning violence prevention. The transcribed interviews were analysed according to Mayring's qualitative content analysis. Results Participants described environmental (e.g., alarm systems), organisational (e.g., security service), and individual-focused measures (staff training, verbal de-escalation). Measures perceived as effective were, for instance, communication and security service. Both demands and barriers were often related to financial constraints, e.g., staff shortage led to higher workloads and less time to consider violence prevention. In most cases, guidelines or standard operating procedures (SOPs) regarding violence prevention were missing, unknown, or not perceived as helpful in their current form. Furthermore, screening tools were not applied in any of the EDs. Conclusions The workload in EDs needs to be decreased in order to enable violence prevention, e.g., by reducing patient inflow or by increasing personnel. In addition, violence prevention guidelines tailored to the requirements of the respective ED need to be developed. Hospitals should supply ED staff with such guidelines, e.g., in the form of SOPs, but more importantly, prevention measures have to be practiced and communicated. Furthermore, there is a need for research on the implementation of screening tools for violent behaviour, so that the focus would shift from managing violence to preventing violence.